Verification of the Cross Immunoreactivity of A60, a Mouse Monoclonal Antibody against Neuronal Nuclear Protein - Mao, Shanping; Xiong, Guoxiang; Zhang, Lei; Dong, Huimin; Liu, Baohui; Cohen, Noam A.; Cohen, Akiva S. (Frontiers in Neuroanatomy, 2016)
A60, the mouse monoclonal antibody against the neuronal nuclear protein (NeuN), is the most widely used neuronal marker in neuroscience research and neuropathological assays. Previous studies identified fragments of A60-immunoprecipitated protein as Synapsin I (Syn I), suggesting the antibody will demonstrate cross immunoreactivity. However, the likelihood of cross reactivity has never been verified by immunohistochemical techniques. Using our established tissue processing and immunofluorescent staining protocols, we found that A60 consistently labelled mossy fiber terminals in hippocampal area CA3. These A60-positive mossy fiber terminals could also be labelled by Syn I antibody. After treating brain slices with saponin in order to better preserve various membrane and/or vesicular proteins for immunostaining, we observed that A60 could also label additional synapses in various brain areas. Therefore, we used A60 together with a rabbit monoclonal NeuN antibody to confirm the existence of this cross reactivity. We showed that the putative band positive for A60 and Syn I could not be detected by the rabbit anti-NeuN in Western blotting. As efficient as Millipore A60 to recognize neuronal nuclei, the rabbit NeuN antibody demonstrated no labelling of synaptic structures in immunofluorescent staining. The present study successfully verified the cross reactivity present in immunohistochemistry, cautioning that A60 may not be the ideal biomarker to verify neuronal identity due to its cross immunoreactivity. In contrast, the rabbit monoclonal NeuN antibody used in this study may be a better candidate to substitute for A60.